2020
DOI: 10.1200/jco.2020.38.15_suppl.6035
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for preinvasive cervical cancer.

Abstract: 6035 Background: Photodynamic therapy (PDT) is an effective treatment for various cancers ensuring maximum preservation of the viability of healthy tissues surrounding the tumor. The purpose of the study was to reveal the effectiveness of PDT in treatment for preinvasive cervical cancer. Methods: The study included 45 patients aged 22-53 years with preinvasive cervical cancer. The patients were divided into two groups depending on the type of the transformation area and the tumor site: group 1–on the exocervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“… 5 Since PDT is a very specific non-invasive localized treatment, with very few side effects and it has a short healing time with no scarring, as well as being suitable for repeated dosing, with little to no resistance being found, it seems to be a far more advantageous treatment for CC. 6 Current clinical phase studies by Gunaydin et al (2021), Li et al (2020), Afanasiev et al (2021) and van Straten et al (2017) have reported that CC ALA PS PDT has emerged as the most effective and harmless treatment strategy for the current control of CC, however it requires further investigation before this treatment can be marketed. 7 - 10 Additionally, even though the latest CC PDT clinical trials have shown the enormous potential, other preclinical trials indicate that there is still room for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Since PDT is a very specific non-invasive localized treatment, with very few side effects and it has a short healing time with no scarring, as well as being suitable for repeated dosing, with little to no resistance being found, it seems to be a far more advantageous treatment for CC. 6 Current clinical phase studies by Gunaydin et al (2021), Li et al (2020), Afanasiev et al (2021) and van Straten et al (2017) have reported that CC ALA PS PDT has emerged as the most effective and harmless treatment strategy for the current control of CC, however it requires further investigation before this treatment can be marketed. 7 - 10 Additionally, even though the latest CC PDT clinical trials have shown the enormous potential, other preclinical trials indicate that there is still room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“… 5 PDT has numerous advantages over conventional therapies, since it is a very specific non-invasive localized treatment, with very few side effects, it has a short healing time with no scarring, and it is highly tolerant to repeated doses with little to no resistance. 6 Furthermore, PDT may be considered for patients as an alternative treatment, as it allows them to preserve their fertility, whereas surgery, chemo- and radiotherapy often induce sterility in patients. 5 …”
Section: Alternative Photodynamic Therapy For Cervical Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of Infectious disease using PDT is a relatively recent application that does not discriminate between strains that are and are not resistant to antibiotics [ 51 , 52 ]. PDT requires a photosensitiser or pro-drug to be applied topically, intravenously or by an expanding range of other routes including oral, intra-auricular injection and transvaginal fibre [ 53 ]. In wound infection and healing, it is vital that the photosensitiser is applied topically to maximally preserve vasculature to the site [ 54 ]-residual product in the proximal capillaries and arterioles following systemic delivery could lead to their destruction during illumination of a site with deeply penetrating light.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 With the development of clinical treatment, photodynamic therapy (PDT) has drawn more and more attention due to the unique advantages of noninvasiveness, spatiotemporal accuracy and synergism. [3][4][5][6][7] The photosensitizers (PSs), as crucial elements, can transfer the endogenous oxygen to reactive oxygen species (ROS) for therapy. [8][9][10][11][12] In particular, benzo[a]phenoselenazinium (NBSe) has potential for efficient cancer phototherapy, thanks to its ultrahigh singlet oxygen quantum yield (F D ) in light and nontoxicity in the dark.…”
Section: Introductionmentioning
confidence: 99%